Development of a water refractive index-matched microneedle integrated into a light sheet microscopy system for continuous embryonic cell imaging. Issue 3 (24th December 2021) - Fan, Yu-Jui; Hsieh, Han-Yun; Huang, Yen-Ru; Tsao, Chieh; Lee, Chia-Ming; Tahara, Hidetoshi; Wu, Yi-Chun; Sheen, Horn-Jiunn; Chen, Bi-Chang
Abstract : Leveraging advances in microfluidics and light sheet imaging technology. We developed a water refractive index-matched microneedle to catch embryos for live imaging. Abstract : In this study, microneedle-integrated light sheet microscopy (LSM) was developed for trapping and continuously imaging embryos of Caenorhabditis elegans with subcellular resolution. To reduce aberrations when the light sheet was propagated into the device, a microneedle was fabricated using a transparent, water refractive index-matched polymer. It was proven that when the light sheet emerged from the water-immersed objective and penetrated through the microneedle with a circular surface, even with a non-perpendicular incident angle, fewer aberrations were found. An embryo was injected into and trapped at the tip of the microneedle, which was positioned at the interrogation window of the LSM apparatus with the image plane perpendicular to the light sheet, and this setup was used to sequentially acquire embryo images. By applying the light sheet, higher-resolution, higher-contrast images were obtained. The system also showed low photobleaching and low phototoxicity to embryos of C. elegans . Furthermore, three-dimensional embryo images with a whole field of view of the microneedle could be achieved by stitching together images and reconstructing sequential two-dimensional embryo images.